(untitled) (Annals of Medical Research, 2023)
Aim: Attention deficit hyperactivity disorder (ADHD) and suicidal behavior are common situations that cause social and emotional problems. deficiencies of folate and vitamin B12 have been related to suicidal behavior and the etiology of ADHD. We aimed to evaluate the association between suicide/self-mutilation behaviors and Vitamin B12 and folic acid levels in adult ADHD. Materials and Methods: Adult ADHD patients were evaluated in terms of sociodemographic characteristics and suicidal behavior/self-mutilation, suicide ideation, impulsivity, and functionality with clinical interviews and scales. Comorbid psychiatric diagnoses were excluded. Levels of vitamin B12 and folate were detected. All results were compared to healthy controls statistically. Then ADHD patients were divided into two groups with and without suicidal behavior/self-mutilation and compared clinically. Results: There were 40 ADHD patients and 40 healthy controls in the study. Suicidal behavior/self-mutilation, suicide ideation and impulsivity scores and psychiatric diagnosis history of first-degree relatives were higher in the patient group. Levels of Vitamin B12 and folic acid were similar in both groups and not correlated with suicidal behavior/self-mutilation and suicidal ideation. Conclusion: There was a significant association between adult ADHD and suicidal behavior/self-mutilation. Suicide-related consequences were particularly related to impulsivity. It may be recommended to screen individuals with ADHD for suicidal ideation and impulsivity to reduce risky behaviors. However, it does not support the hypothesis of a relationship between low B12 and folate and suicidality in adult ADHD.